A leadership competence framework for sustainable development in the manufacturing industry in a developing country context: the bicycle metaphor - Eliot Quinz Farai Ruwanika; Liezel Massyn (Cogent Business & Management, 2024)
The article presents a leadership competence framework for sustainable development (LCFSD) contextualized to the United Nations' Sustainable Development Goals (SDGs), to drive businesses to contribute to the achievement of these goals. A synthesis of metatheories and leadership theories produced a three-pillar draft leadership competence framework (LCF) that informed the field enquiry. Face-to-face interviews were conducted with 12 executives (five CEOs; six executives; one former executive) in the beverage manufacturing industry in Zimbabwe using the snowball sampling technique. Data were transcribed and analysed thematically. The results were incorporated in the development of a reconstructed LCF. Four experts validated the LCFSD, confirming its applicability and transferability; thus, their suggestions were incorporated. The outcome is a LCFSD depicted by a bicycle metaphor comprising five pillars, namely strategic competences (presencing, intergenerational systemic behaviour, reflexivity, stakeholder engagement, strategic awareness, sustainability thinking, knowledge of metrics of measurement, inclusivity skills, multiple leadership styles); core competences (social responsiveness, ecosystem thinking, self-leadership, knowledge of SDGs, innovative thinking); core values (ethical; caring for all, respect for all, doing the best for local communities, diplomacy, beliefs in sustainable development); collaborative competences (build diverse teams, partnering skills); and person-leader competencies (leadership competences at exercised at personal level).
Keywords: 650; Leadership competence framework; sustainable development; SDGs